2018
DOI: 10.1038/s41598-018-29821-9
|View full text |Cite
|
Sign up to set email alerts
|

Fouling Development in A/O-MBR under Low Organic Loading Condition and Identification of Key Bacteria for Biofilm Formations

Abstract: Membrane fouling in membrane bioreactors (MBR) remains a major issue and knowledge of microbes associated with biofilm formation might facilitate the control of this phenomenon, Thus, an anoxic/oxic membrane bioreactor (A/O-MBR) was operated under an extremely low organic loading rate (0.002 kg-COD·m−3·day−1) to induce membrane fouling and the major biofilm-forming bacteria were identified. After operation under extremely low organic loading condition, the reactor showed accumulation of total nitrogen and phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…It has been reported that bioflocculation could be beneficial to membrane fouling reduction in conventional MBRs ( Van den Broeck et al, 2012), its impact in NF-MBRs will be discussed in Section 5.3.3. (Takimoto et al, 2018, Jo et al, 2016, Xia et al, 2012. Also, the microbial communities in both NF-MBRs had comparable relative abundances (Figure 5-7) with similar observed OTU, Chao1, Shannon and Simpson diversity indexes (Table 5-5).…”
Section: Impact Of Salt Accumulation On Biomass Characteristicssupporting
confidence: 59%
“…It has been reported that bioflocculation could be beneficial to membrane fouling reduction in conventional MBRs ( Van den Broeck et al, 2012), its impact in NF-MBRs will be discussed in Section 5.3.3. (Takimoto et al, 2018, Jo et al, 2016, Xia et al, 2012. Also, the microbial communities in both NF-MBRs had comparable relative abundances (Figure 5-7) with similar observed OTU, Chao1, Shannon and Simpson diversity indexes (Table 5-5).…”
Section: Impact Of Salt Accumulation On Biomass Characteristicssupporting
confidence: 59%
“…The 16 s rDNA library preparation, sequencing, and data analysis were carried out based on a previous report. 32 Sequencing methods are described in detail in the Supporting Information . Metagenomic sequencing data were analyzed with the Quantitative Insights Into Microbial Ecology software (version 1.9.1).…”
Section: Methodsmentioning
confidence: 99%
“…The 16 s rDNA library preparation, sequencing, and data analysis were carried out based on a previous report . Sequencing methods are described in detail in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Fouling occurs due to the accumulation of pollutants in wastewater and the formation of biofilms by activated sludge [ [11] , [12] , [13] ]. In recent years, many studies on the modification of membrane material by mixing zeolite into the membrane to increase the flux have been reported.…”
Section: Introductionmentioning
confidence: 99%